PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN BERMOTOR - Watriningsi Watriningsi; Amrico Simon Carlos (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The aim of the writer is to do this research to find out whether there are effects of product quality, price and promotion with purchasing decisions. From the results of observations made by the authors it turns out that purchasing decisions can be influenced by product quality, price, and promotion. The method of data collection for this research is by distribusing surveys and questionnaires, data analytical technic by the validity test, reliability, normality test, homogeneity test, and regression analytic test using a tool help with the SPSS program version 19. After doing research and through the process of data analysis obtained the results that the quality of products, prices, and promotions have a significant effect on increasing purchasing decisions, based on the results of the calculation of the f test obtained f count value of 62.889. F count value is greater than f table. The coefficient of determination R2 is 0.771, meaning the variation of the purchase decision variable can be explained by variations in the variables of product quality, price, and promotion by 77.1%, while the remaining 22.9% is explained by other variables outside the regression model.